2020
DOI: 10.1016/j.phrs.2020.104821
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics analysis of COVID-19 in the surrounding areas of Wuhan, Hubei Province in 2020

Abstract: , new COVID-19 outbreaks have occurred and spread around the world. However, the clinical characteristics of patients in other areas around Wuhan, Hubei Province are still unclear. In this study, we performed epidemiological and clinical characteristics analysis on these regional cases. Methods: We retrospectively investigated COVID-19 patients positively confirmed by nucleic acid Q-PCR at Taihe Hospital from January 16 to February 4, 2020. Their epidemiological, clinical manifestations, and imaging characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 20 publications
3
47
1
7
Order By: Relevance
“…More findings by Kim et al [42] in a recent Korean cohort study with 28 hospitalized patients with confirmed COVID-19 in which only 5 of the patients out of 27 (18.5%) had any smoking history. Another study by Zheng et al [43] reported that only 10.9% of all patients in the study were smokers, but 6.7% were smokers in the severe/critically ill group, which is not significantly (χ 2 = 0.962, p > 0.05) lower than of the ordinary group with 14.0%. They further concluded that no evidence exists that smoking protects COVID-19 patients from developing to severe disease.…”
Section: The Epidemiology Of Smoking and Covid-19mentioning
confidence: 60%
“…More findings by Kim et al [42] in a recent Korean cohort study with 28 hospitalized patients with confirmed COVID-19 in which only 5 of the patients out of 27 (18.5%) had any smoking history. Another study by Zheng et al [43] reported that only 10.9% of all patients in the study were smokers, but 6.7% were smokers in the severe/critically ill group, which is not significantly (χ 2 = 0.962, p > 0.05) lower than of the ordinary group with 14.0%. They further concluded that no evidence exists that smoking protects COVID-19 patients from developing to severe disease.…”
Section: The Epidemiology Of Smoking and Covid-19mentioning
confidence: 60%
“…A total of 3.8% of confirmed COVID-19 patients were health workers (Aggarwal, Lippi & Michael Henry, 2020). Diabetes could be one of the risk factors for progression to severe/critical outcomes (Zheng et al, 2020). Human-human transmission is considered a major transmission mode of COVID-19 by the sixth version of the Guidance for Diagnosis and Treatments for COVID-19 issued by the National Health Commission of China.…”
Section: Epidemiologic Features Of the Three Virusesmentioning
confidence: 99%
“…According to a study among 138 hospitalized patients with 2019 novel coronavirus-infected pneumonia in Wuhan, China, the male-to-female ratio was 1.06:1, and the median age was 56 years (interquartile range, 42–68; range, 22–92 years) ( Wu & McGoogan, 2020 ; Wang et al, 2020 ). Of the 1,591 patients requiring treatment in an intensive care unit (ICU) in the Lombardy region of Italy, the median (IQR) age was 63 ( Richardson et al, 2020 ; Borghesi et al, 2020 ; Zheng et al, 2020 ; De Wit et al, 2016 ; Gao et al, 2016 ) years, and 1,304 (82%) were male ( Grasselli et al, 2020 ). According to the data from 5,700 hospitalized patients with confirmed COVID-19 in New York City, the median age was 63 years (interquartile range, 52–75; range, 0–107 years), and 39.7% were female ( Richardson et al, 2020 ).…”
Section: Biological and Epidemiologic Features Of The Three Virusesmentioning
confidence: 99%
“…This scenario clearly suggests that the clinical profile of potentially infected subjects is crucial in the knowledge and prompt diagnosis of COVID-19. In this respect, comorbidities and clinical signs of COVID-19 patients have been included in epidemiological studies, although reported mainly as descriptive statistics [2,[4][5][6][7][8][9][10][11][12][13] even in very large investigations [14].…”
Section: Introductionmentioning
confidence: 99%